Industrial fuel ethanol yeasts contain adaptive copy number changes in genes involved in vitamin B1 and B6 biosynthesis - Stambuk, Boris U.; Dunn, Barbara; Alves, Sergio L.; Duval, Eduarda H.; Sherlock, Gavin (Genome Research, 2009)
Fuel ethanol is now a global energy commodity that is competitive with gasoline. Using microarray-based comparative genome hybridization (aCGH), we have determined gene copy number variations (CNVs) common to five industrially important fuel ethanol Saccharomyces cerevisiae strains responsible for the production of billions of gallons of fuel ethanol per year from sugarcane. These strains have significant amplifications of the telomeric SNO and SNZ genes, which are involved in the biosynthesis of vitamins B6 (pyridoxine) and B1 (thiamin). We show that increased copy number of these genes confers the ability to grow more efficiently under the repressing effects of thiamin, especially in medium lacking pyridoxine and with high sugar concentrations. These genetic changes have likely been adaptive and selected for in the industrial environment, and may be required for the efficient utilization of biomass-derived sugars from other renewable feedstocks.